THE EXPRESSION OF PIETY THROUGH THE RATIK TOGAK IN THE TAREKAT SURAU SULUK IN RIAU - Toni Hartono; Imron Rosidi; Roni Setia Nugraha (Sosiohumaniora, 2020)
Tarekat is piety expression based on spirituality encouragement as Islamic identity in Indonesia. Studies about piety expression is often connected to redicalism or violent movement. In fact, piety expression of Muslims in Indonesia as described in this article can accomodate with local culture. This study examines the existence of Surau Suluk and the tradition of Ratik Togak, which is one of the practices of the Naqsabandiyah tarekat in Rokan Hulu. It is known ‘Negeri Seribu Suluk’, having approximately 122 Surau Suluk. Surau Suluk is a place to undergo religious activities to get closer to God. This study uses qualitative descriptive method employing observation and interview. A phenomenological concept is used to see the religious traditions of followers of the Surau Suluk congregation. The results showed that Surau Suluk in Rokan Hulu is developed by Sheikh Abdul Wahab Rokan. A practice that has become a tradition in the Naqsabandiyah tariqah is Ratik Togak. Ratik means dhikr, a practice in the form of dhikr and forgiveness which is done to find the peak of enjoyment of dhikr. The Togak Ratik is performed at certain religious events in public spaces as an important medium for them to get closer to God. Ratik Togak is a form of social Islamic religious worship. This tradition is special because it has become an icon for Surau Suluk which involves ordinary people. It also gets support from local government. This tradition is a practice for followers of the Naqsabandiyah as a form of their piety with God.